AN HR MANAGER CONFRONTING CHALLENGE OF CHANGE (CASE STUDY ON EMPLOYEE ATTENDANCE MANAGEMENT) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
It is a widely held age old belief that attendance  system plays a vital role in an organization as it  defines its employee productivity. On the other  hand the changing business landscape is posing  multiple challenges to the modern day managers  to confront. In order to boldly face the challenges  and attain competitive edge many companies are  on an innovation spree and hence challenging  the stereotypes. The present case is related to a  more than six decade old textile company’s HR  head’s dilemma of whether to continue its struggle  for a better attendance management system? or  doing away with it, as has been done by a few  other companies. Exhibits help corroborate and  supplement the information presented in the case.  End of the case poses certain questions, answers  of which can be discussed in the classroom with  the help of teaching notes.
Keywords: Attendance management; Biometric; Showcard; Human Resource Management